RF and microwave modeling and measurement techniques for compound field effect transistors - Gao, Jianjun 1968- (SciTech Publishing, 2010)
This book combines both measurement technique and its application in an example of compound semiconductor FETs. The book shows an approach of how to take the measurement and based on the measurement data, to start the small signal, nonlinear modeling, and parameter extraction for the devices. The book includes all detailed information for FETs, which seldom appears in other books like this, therefore this should be helpful for new researchers making their way in their career. Even for those without a good microwave background, the contents of this book can be easily understood. The presentation of this book assumes only a basic course in electronic circuits as a prerequisite. Instead of using electromagnetic fields like much of the microwave engineering books, the subject is introduced via circuit concepts.